2021
DOI: 10.1136/medethics-2020-107202
|View full text |Cite
|
Sign up to set email alerts
|

Survey of German medical students during the COVID-19 pandemic: attitudes toward volunteering versus compulsory service and associated factors

Abstract: Due to the spread of COVID-19, a key challenge was to reduce potential staff shortages in the healthcare sector. Besides recruiting retired healthcare workers, medical students were considered to support this task. Commitment of medical students in Germany during the COVID-19 pandemic was evaluated using an online survey, with particular focus on their burdens and anxieties. This survey was distributed to students within a 2-week period in April and May 2020. Ultimately, 1241 participants were included in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…A chain-mediation analysis of this phenomenon outlined four essential topics: altruistic motivation, prosocial encouragement, self-moral cognition, and reward ( 42 ). Included studies showed that in terms of gender, female students ( 21 , 24 , 39 , 43 , 44 ) were more likely to be involved in the pandemic control and volunteering than males ( 35 , 40 , 41 ), with a willingness proportion of 60.2% (female) vs. 52.3% (male).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A chain-mediation analysis of this phenomenon outlined four essential topics: altruistic motivation, prosocial encouragement, self-moral cognition, and reward ( 42 ). Included studies showed that in terms of gender, female students ( 21 , 24 , 39 , 43 , 44 ) were more likely to be involved in the pandemic control and volunteering than males ( 35 , 40 , 41 ), with a willingness proportion of 60.2% (female) vs. 52.3% (male).…”
Section: Resultsmentioning
confidence: 99%
“…Following the positive impression of volunteering activity, three studies found a high level of willingness (73.2–94%) among health professional students regarding participation in the future ( 7 , 49 , 53 ). Regarding mental issues associated with volunteering, four studies found that student volunteers had low psychological stress ( 40 , 44 , 51 , 55 ). The prevalence of anxiety and depression was lower among volunteering students than non-volunteering ones, indicating that it positively influenced general psychological wellbeing ( 40 , 51 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our sample, more than half of volunteering students feared getting infected before and during their volunteering tasks, and more than 70% feared infecting their relatives or friends. Mihatsch et al, and Zhang et al, also reported that students were more concerned about infecting other patients and relatives than themselves [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the event of COVID-19 infection, 42% of medical students felt that they would recover without hospitalization [ 13 ]. Mihatsch et al, and Zhang et al, also reported that students were more concerned about infecting other patients and relatives than themselves [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%